La „saevitia” de Quintilius Varus: transformación de su imagen entre Velleius Paterculus y L. Annaeus Florus - González-Conde, Maria Giovanna (Acta Classica Universitatis Scientiarum Debreceniensis, 2020)
In Latin literature the image of Quintilius Varus underwent an evolution between Velleius Paterculus and Florus that to a large extent corresponded to the change of political circumstances within the Roman state. During the reign of Tiberius the “clades Variana” was devised as a means that helped justify to public opinion the changes in foreign policy. A century later, Annaeus Florus, who had lived through Trajan’s wars, described the “saevitia” of Varus and attacked the idea of expansion beyond the limes. This attitude provides further support for the case that is now made for his work’s “Hadrianic ideology”.